Long-Term Dietary Folate Deficiency Accelerates Progressive Hearing Loss on CBA/Ca Mice - Martínez-Vega, Raquel; Murillo-Cuesta, Silvia; Partearroyo, Teresa; Varela-Moreiras, Gregorio; Varela-Nieto, Isabel; Pajares, María A. (Frontiers in Aging Neuroscience, 2016)
Dietary folic acid deficiency induced early hearing loss in C57BL/6J mice after two-months, corroborating the epidemiological association previously described between vitamin deficiency and this sensory impairment. However, this strain is prone to early hearing loss, and hence we decided to analyze whether the effects exerted by folate deprivation follow the same pattern in a mouse strain such as CBA/Ca, which is resistant to hearing impairment. Here, we show results of a long-term study on hearing carried out on CBA/Ca mice subjected to dietary folate deprivation. Systemic changes included decreased serum folate levels, hyperhomocysteinemia and signs of anemia in the group fed the folate-deficient diet. Initial signs of hearing loss were detected in this strain after 8-months of vitamin deficiency, and correlated with histological damage in the cochleae. In conclusion, the data presented reinforce the importance of adequate folic acid levels for the auditory system and suggest that the impact of dietary deficiencies may depend on the genetic background.